Suppression of Macrophage Migration and M2 Polarization by an Ethanolic Extract of Scutellaria baicalensis Root - Hyun-Ji Park; Shin-Hyung Park (Journal of Pharmacopuncture)
Objectives: The root of Scutellaria baicalensis (SB) exhibits various pharmacological activities, including anticancer effects. This study aimed to investigate the anticancer effects of the ethanolic extract of SB root (ESB), with a particular focus on its regulatory influence on tumor-associated macrophages (TAMs). Methods: The effect of ESB on macrophage migration was evaluated using a transwell migration assay. Conditioned medium (CM) derived from lung cancer cells was used as a chemoattractant. M2 macrophage polarization was assessed by measuring the IL-4- or IL-6-induced expression of M2 macrophage markers (CD206, arginase-1, and IL-10) via realtime PCR. The phosphorylation of signal transducer and activator of transcription 3 (STAT3) was analyzed by Western blotting. The effect of ESB-regulated M2 polarization on lung cancer cell migration was evaluated using a transwell migration assay with CM from macrophages. Results: ESB significantly inhibited the migration of both RAW 264.7 and THP-1 macrophages. In addition, ESB suppressed IL-4- and IL-6-induced M2 macrophage marker expression and reduced STAT3 phosphorylation, indicating the inhibition of macrophage polarization into the M2 phenotype. Furthermore, CM from M2-polarized RAW 264.7 cells enhanced Lewis lung carcinoma (LLC) cell migration, whereas CM from RAW 264.7 cells co-treated with ESB and IL-6 markedly reversed this effect. Conclusion: These findings suggest that ESB attenuates macrophage migration and prevents M2 macrophage polarization, leading to the suppression of lung cancer cell migration. These results highlight the potential of ESB as an anticancer agent targeting TAMs.